Protein kinase C‐delta inhibition is organ‐protective, enhances pathogen clearance, and improves survival in sepsis. Issue 2 (23rd December 2019) - Liverani, Elisabetta; Tursi, Sarah A.; Cornwell, William D.; Mondrinos, Mark J.; Sun, Shuang; Buttaro, Bettina A.; Wolfson, Marla R.; Rogers, Thomas J.; Tükel, Çagla; Kilpatrick, Laurie E.
Abstract: Sepsis is a leading cause of morbidity and mortality in intensive care units. Previously, we identified Protein Kinase C‐delta (PKCδ) as an important regulator of the inflammatory response in sepsis. An important issue in development of anti‐inflammatory therapeutics is the risk of immunosuppression and inability to effectively clear pathogens. In this study, we investigated whether PKCδ inhibition prevented organ dysfunction and improved survival without compromising pathogen clearance. Sprague Dawley rats underwent sham surgery or cecal ligation and puncture (CLP) to induce sepsis. Post‐surgery, PBS or a PKCδ inhibitor (200µg/kg) was administered intra‐tracheally (IT). At 24 hours post‐CLP, there was evidence of lung and kidney dysfunction. PKCδ inhibition decreased leukocyte influx in these organs, decreased endothelial permeability, improved gas exchange, and reduced blood urea nitrogen/creatinine ratios indicating organ protection. PKCδ inhibition significantly decreased bacterial levels in the peritoneal cavity, spleen and blood but did not exhibit direct bactericidal properties. Peritoneal chemokine levels, neutrophil numbers, or macrophage phenotypes were not altered by PKCδ inhibition. Peritoneal macrophages isolated from PKCδ inhibitor‐treated septic rats demonstrated increased bacterial phagocytosis. Importantly, PKCδ inhibition increased survival. Thus, PKCδ inhibition improved survival and improved survival was associated with increased phagocytic activity, enhanced pathogen clearance, and decreased organ injury.